HPLC Validation of Phyllanthin, it's Seasonal Variation in Phyllanthus fraternus and Evaluation of the Procurement Time - Narasimhaji, Ch. Venkata; Singh, Ravindra; Mangal, Anupam; Prabu, Rekha; Marimuthu, Gokul; Ilavrasan, R.; Srikanth, Narayanam (Indian Forester, 2022)
Medicinal plants efficacy for various activities, depends on the nature of primary, secondary metabolites and presence of its degree of quantity. The concentrations of secondary metabolites play a vital role for medicinal properties. The amount of secondary metabolites directly related with the growth of the herbs or plants, certainly depends on the collection time of the plant materials for which parts and in which season they are acquired. Hence it is important to find out the best season for the collection of raw botanical materials for its desired therapeutic action in an effective manner and it is aimed to evaluate the best harvesting time for Phyllanthus fraternus whole plant in terms of assay of phyllanthin though HPLC.